Upaya Peningkatan Literasi-Numerasi Peserta Didik dengan Pembuatan Pojok Baca dan Majalah Dinding Berhitung Kelas 5 di SD Negeri Pilang 1 - Sriwijayanti, Ribut Prastiwi; Putri, Dita Refani; Festawanti, Errina Dinda; Sholeha , Rita; Miranda , Iwing Ade; Maulidiana, Firli; P.T.K, Rr. Ghina Ayu; Alfaruqi, Moh. Umar (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Literacy and Numeracy are things that are not common in the world of education. Literacy and numeracy are needed when implementing the learning process in the classroom to increase students' insight in receiving learning. Therefore, as teachers must have innovation so that students can improve literacy and numeracy, for example by using interesting learning media as student insights. This article was created with the aim of improving students' literacy and numeracy by creating reading corners and counting mading in the classroom using qualitative research methods of classroom actions and case studies with data collection carried out through class observation and class AKM tests. The results obtained from the writing and implementation of this article achieved results with an average of 78 literacy competencies and 80 for numeracy competencies.